762 Mental health morbidity among medical and surgical oncology residents. (24th April 2018) - Fahim, A; Waheed, A; Aly, H
Abstract : Introduction: Oncology clinicians represent stressful occupational category and suffer mental health morbidity. They are exposed to the clinical stressors and emotional demands related to care of cancer patients and their families, and feel worried about their career future. The present study was conducted to assess some aspects of mental health among medical and surgical oncology residents. Methods: This survey was conducted to assess some mental health aspects among residents, who have at least 1 year of work experience at both medical and surgical oncology departments. All participants were asked to complete a questionnaire. The questionnaire was based on items that included General Health Questionnaire (GHQ-12) to assess psychological distress; Symptom Checklist for Depression (SCD) to measure depression; and questions about demographic and occupational data. Logistic regression was used to assess the association between potential predictor variables of GHQ and SCD, results were considered statistically significant when p-value less than 0.05 Results: Thirty seven physicians responded (response rate 91.3%). Levels of psychological distress and depression were measured by GHQ and SCD. Eleven physicians (29.7%, 95% CI; 17.3–45.7) scored >3 on GHQ indicating psychological distress, and 37.8% (95% CI: 24.1 to 53.9) scored ≥1.5 on SCD indicative of depression. Suicidal thoughts were reported by 3 residents. The effect of occupational stress was the main predictor of both psychological distress and depression. Conclusion: Stress needs to be managed among physicians in such specialties to have a satisfactory professional life and high job productivity.